Modern design in wood - Stewart, Richard (London : John Murray, 1984)
Contiene: acknowledgments, sculpture and jewellery, woodware, toys and recreational equipment, stools, chairs and settees, tables and dining suites, cabinets, desks and sideboards, modular and fitted furmiture